2020
DOI: 10.1049/iet-pel.2019.0408
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative switched‐inductor/capacitor type DC–DC converter with large voltage gain for PV applications

Abstract: In grid-connected PV applications, the presence of a transformer not only increases the cost, size and weight, but also decreases the whole system efficiency, especially, under poor irradiation conditions. To eliminate the transformer and to meet DC link voltage, a regenerative switched-inductor/capacitor type DC-DC converter with large voltage gain is proposed in this study. In traditional boost type and derived converters, the voltage gain ratio is limited due to voltage stress on the semiconductor devices a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Another group of step‐up converters is switched‐inductor (SL) circuits that their operation is similar to SC circuits. However, these are involving many inductors that store magnetic energy 19–23 . Utilizing transformers and coupled inductors is also another solution for step‐up dc‐dc conversion 24–28 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another group of step‐up converters is switched‐inductor (SL) circuits that their operation is similar to SC circuits. However, these are involving many inductors that store magnetic energy 19–23 . Utilizing transformers and coupled inductors is also another solution for step‐up dc‐dc conversion 24–28 .…”
Section: Introductionmentioning
confidence: 99%
“…However, these are involving many inductors that store magnetic energy. [19][20][21][22][23] Utilizing transformers and coupled inductors is also another solution for step-up dc-dc conversion. [24][25][26][27][28] Higher gains are achieved due to the transformer/coupled inductor winding coefficient.…”
mentioning
confidence: 99%
“…Faridpak et al 35 added passive switched inductor, active switched inductor, and switched capacitor cells to conventional boost topologies, whose results indicated that its voltage gain and efficiency could be improved by utilizing the above structures. Karthikeyan et al 36 put forward a regenerative switched‐inductor/capacitor type DC–DC converter with large voltage gain, whose results indicated that this topology possessed smooth continuous current and the energy in lossless passive components could be recycled. Elsayad et al 37 presented a single‐switch transformerless boost DC–DC converter, which was composed of a switched‐capacitor multiplier and an integrated LC 2 D output network, and it could be seen that this structure had a wide voltage gain range to suit the wide voltage swings of fuel cells.…”
Section: Introductionmentioning
confidence: 99%
“…The converter utilises more components. Later, different converter topologies are described to attain high‐voltage gain based on the modified SL and SC networks [7–9]. Recently, a converter topology using nine components is also reported to achieve the voltage gain of (1 + D )/(1 − D ) [10].…”
Section: Introductionmentioning
confidence: 99%